Pressure flaking to serrate bifacial points for the hunt during the MIS5 at Sibudu Cave (South Africa) - (:unkn) unknown (My University, 2017)
Projectile technology is considered to appear early in the southern African Middle Stone Age (MSA) and the rich and high resolution MSA sequence of Sibudu Cave in KwaZulu-Natal has provided many new insights about the use and hafting of various projectile forms. We present the results of a functional and technological analysis on a series of unpublished serrated bifacial points recently recovered from the basal deposits of Sibudu Cave. These serrated tools, which only find equivalents in the neighbouring site of Umhlatuzana, precede the Still Bay techno-complex and are older than 77 ka BP. Independent residue and use-wear analyses were performed in a phased procedure involving two separate analysts, which allowed the engagement between two separate lines of functional evidence. Thanks to the excellent preservation at Sibudu Cave, a wide range of animal, plant and mineral residues were observed in direct relation with diagnostic wear patterns. The combination of technological, wear and residue evidence allowed us to confirm that the serration was manufactured with bone compressors and that the serrated points were mounted with a composite adhesive as the tips of projectiles used in hunting activities. The suite of technological and functional data pushes back the evidence for the use of pressure flaking during the MSA and highlights the diversity of the technical innovations adopted by southern African MSA populations. We suggest the serrated points from the stratigraphic units Adam to Darya of Sibudu illustrate one important technological adaptation of the southern African MSA and provide another example of the variability of MSA bifacial technologies.
Keywords: African Research